Scaling Up Hepatitis C Prevention and Treatment Interventions for Achieving Elimination in the United States: A Rural and Urban Comparison. Issue 8 (31st May 2019) - Fraser, Hannah; Vellozzi, Claudia; Hoerger, Thomas J; Evans, Jennifer L; Kral, Alex H; Havens, Jennifer; Young, April M; Stone, Jack; Handanagic, Senad; Hariri, Susan; Barbosa, Carolina; Hickman, Matthew; et al.
Abstract: In the United States, hepatitis C virus (HCV) transmission is rising among people who inject drugs (PWID). Many regions have insufficient prevention intervention coverage. Using modeling, we investigated the impact of scaling up prevention and treatment interventions on HCV transmission among PWID in Perry County, Kentucky, and San Francisco, California, where HCV seroprevalence among PWID is >50%. A greater proportion of PWID access medication-assisted treatment (MAT) or syringe service programs (SSP) in urban San Francisco (established community) than in rural Perry County (young, expanding community). We modeled the proportion of HCV-infected PWID needing HCV treatment annually to reduce HCV incidence by 90% by 2030, with and without MAT scale-up (50% coverage, both settings) and SSP scale-up (Perry County only) from 2017. With current MAT and SSP coverage during 2017–2030, HCV incidence would increase in Perry County (from 21.3 to 22.6 per 100 person-years) and decrease in San Francisco (from 12.9 to 11.9 per 100 person-years). With concurrent MAT and SSP scale-up, 5% per year of HCV-infected PWID would need HCV treatment in Perry County to achieve incidence targets—13% per year without MAT and SSP scale-up. In San Francisco, a similar proportion would need HCV treatment (10% per year) irrespective of MAT scale-up. Reaching the same impact by 2025 would require increases in treatment rates of 45%–82%. Achievable provision of HCV treatment, alongside MAT and SSP scale-up (Perry County) and MAT scale-up (San Francisco), could reduce HCV incidence.